2013
DOI: 10.1002/pbc.24322
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index at diagnosis or weight change during therapy predict toxicity or survival in intermediate risk rhabdomyosarcoma? A report from the Children's Oncology Group soft tissue sarcoma committee

Abstract: Background Weight loss prevalence and its impact on toxicities and survival in intermediate risk rhabdomyosarcoma (IRMS) patients are unknown. We evaluated the association between weight change during therapy and number of toxicities, hospital days, infections, and overall survival and between baseline body mass index (BMI) and survival in patients treated on Children’s Oncology Group trial D9803. Procedure Four hundred sixty-eight IRMS patients age ≥2 and <21 years treated on D9803 had required data. Regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Abundant evidence exists regarding the negative impact that abnormal pre‐diagnosis weight, and particularly obesity, has on treatment outcome in several types of malignant diseases in adults . More recently studies of the pediatric cancer population showed similar results . It is unclear what the causes responsible for these observations are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant evidence exists regarding the negative impact that abnormal pre‐diagnosis weight, and particularly obesity, has on treatment outcome in several types of malignant diseases in adults . More recently studies of the pediatric cancer population showed similar results . It is unclear what the causes responsible for these observations are.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some biological factors in the tissues and at the cellular level of obese patients are responsible for the effect . Underweight patients may have a worse prognosis due to higher levels of toxicity during treatment . Chemotherapy‐induced necrosis has proved to be valuable in assessment of tumor chemosensitivity in Ewing sarcoma (EWS) patients .…”
Section: Introductionmentioning
confidence: 99%
“…(35) Patients with low BMI (<5%ile), or those who lose significant weight experience greater toxicity than other children. Patients with low BMI may also have inferior survival.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort of 133 newly diagnosed patients including brain and solid tumor patients showed increased BMI and fat mass within three months of and doubled by 12 months post diagnosis (21). In contrast, weight loss occurred in 37% of 468 patients with intermediate rhabdomyosarcoma, and low baseline BMI correlated with borderline inferior survival (22). Collectively, these data indicate that weight management early during cancer treatment is an opportunity for interventions, and to be successful, a nutritional program needs to be integrated into the clinical care model and must be sustained throughout treatment (23).…”
Section: Diet – Calories Versus Compositionmentioning
confidence: 99%